Digital social movement: Using social media to reject Indonesia's draft criminal code (RUU KUHP) - Michel, Diana; Purwaningsih, Titin; Rahmawati, Dian Eka; Sutan, Arissy Jorgi (Digital Theory, Culture & Society, 2023)
This research tries to explore the use of social media as part of the digital social movement to reject the draft Indonesian Penal Code (RUU KUHP). In this case, social media were used in different social movements. This research uses a qualitative approach to know what kind of value of the phenomena. This research uses analysis Q-DAS (Qualitative Data Analysis Software), which uses social media data, and the tool is Nvivo 12 Plus. This research finds: First, the dominant social media theme is relevant to the legal theme area and aspect. In addition, the social media themes themselves have been made from the content used in social media as a reaction of netizens about the rejection of the Indonesian draft criminal code. Second, the narrative is dominated by the use of hashtags, but some of them use accounts and topics of law. Third, the hashtags have a relationship with other hashtags that tend to be strong, indicating that there are using the hashtag as a marker and possibly using more than 2 hashtags in one post with the same goal to reject the Indonesia Draft Criminal Code.